Longitudinal Evaluation of an Integrated Post–COVID-19/Long COVID Management Program Consisting of Digital Interventions and Personal Support: Randomized Controlled Trial - Christina Derksen; Robin Rinn; Lingling Gao; Alina Dahmen; Cay Cordes; Carina Kolb; Petra Becker; Sonia Lippke (Journal of Medical Internet Research, 2023)
Background The postacute COVID-19 syndrome (PACS) can be addressed with multidisciplinary approaches, including professional support and digital interventions. Objective This research aimed to test whether patients who received a health care facilitation program including medical internet support from human personal pilots and digital interventions (intervention group [IG] and active control group [ACG]) would experience fewer symptoms and have higher work ability and social participation than an untreated comparison group (CompG). The second objective was to compare the impact of a diagnostic assessment and digital interventions tailored to patients’ personal capacity (IG) with that of only personal support and digital interventions targeting the main symptoms (ACG). Methods In total, 1020 patients with PACS were recruited. Using a randomized controlled trial design between the IG and the ACG, as well as propensity score matching to include the CompG, analyses were run with logistic regression and hierarchical-linear models. Results Symptoms decreased significantly in all groups over time (βT1-T2=0.13, t549=5.67, P